A Birth-cohort testing intervention identified hepatitis c virus infection among patients with few identified risks: a cross-sectional study. Issue 1 (December 2015) - Southern, William; Norton, Brianna; Steinman, Meredith; DeLuca, Joseph; Drainoni, Mari-Lynn; Smith, Bryce; Litwin, Alain
Abstract Background International guidelines and U.S. guidelines prior to 2012 only recommended testing for hepatitis C virus (HCV) infection among patients at risk, but adherence to guidelines is poor, and the majority of those infected remain undiagnosed. A strategy to perform one-time testing of all patients born during 1945–1965, birth cohort testing, may diagnose HCV infection among patients whose risk remains unknown. We sought to determine if a birth-cohort testing intervention for HCV antibody positivity helped identify patients with fewer documented risk factors or medical indications than a pre-intervention, risk-based testing strategy. Methods We used a cross-sectional design with retrospective electronic medical record review to examine patients identified with HCV antibody positivity (Ab+) during a pre-intervention (risk-based) phase, the standard of care at the time, vs. a birth-cohort testing intervention phase. We compared demographic and clinical characteristics and HCV risk-associated factors among patients whose HCV Ab + was identified during the pre-intervention (risk-based testing) vs. post birth-cohort intervention phases. Study subjects were patients identified as HCV-Ab + in the baseline (risk-based) and birth-cohort testing phases of the Hepatitis C Assessment and Testing (HepCAT) Project. Results Compared to the risk-based phase, patients newly diagnosed with HCV Ab + after the birth-cohort intervention were significantly less likely to have a history of any substance abuse (30.5 % vs. 49.5 %, p  = 0.02), elevated alanine transaminase levels of > 40 U/L (22.0 % vs. 46.7 %, p  = 0.002), or the compositeany risk-associated factor (55.9 % vs. 79.0 %, p  = 0.002). Conclusions Birth-cohort testing is an useful strategy for identifying previously undiagnosed HCV Ab + because it does not require providers ask risk-based questions, or patients to disclose risk behaviors, and appears to identify HCVAb +  in patients who would not have been identified using a risk-based testing strategy.